Altered Glutamate and Glutamine Kinetics in Autism Spectrum Disorder. (7th June 2021) - De Wandel, Sofie; Engelen, Marielle PKJ; Wierzchowska-McNew, Raven; Thompson, Julie; Kirschner, Sarah K; Cruthirds, Clayton L; Have, Gabriella AM Ten; Thaden, John J; Deutz, Nicolaas EP
Abstract: Objectives: Recent studies suggest that glutamate (GLU) signaling abnormalities are involved in the etiology of Autism Spectrum Disorder (ASD), suggesting perturbations in GLU and glutamine (GLN) metabolism. Although GLU and GLN plasma concentrations have been linked to cognitive decline, the actual production of GLU and GLN have never been measured in ASD and linked to ASD severity score and neurocognitive and mood changes. Methods: 19 young adults with high functioning ASD (age 24.3 ± 1.0y, Autism Quotient (AQ): 31.4 ± 1.7), and 46 control subjects (age 23.4 ± 0.3y)) were enrolled. ASD severity and subscores as well as cognitive function and mood were assessed (MOCA, TMT, word fluency, Stroop, HADS). Postabsorptive amino acid kinetics (production of GLU and GLN, and its interconversion rates (GLU > >GLN and GLN > >GLU)) were measured by pulse stable isotope administration and subsequent blood sampling for 4 hours. Plasma amino acid enrichments and concentrations were analyzed by LC-MS/MS. Stats were done by ANCOVA, post hoc analysis and Pearson correlation. Significance was set at p < 0.05. Results: No differences were present in word fluency, but higher values in ASD for TMTb (p = 0.066), depression (p = 0.0004), anxiety (p = 0.0006) and lower values for MOCA (0.0054). The ASD group was characterized by lower plasma GLN and GLU concentrations (p < 0.05). Although the production rates of GLN and GLU were not different between the groups, in ASD GLN > >GLU was higher (p = 0.0018) and GLU > >GLN lower (p = 0.016) and a higher GLN clearance rate (p = 0.006). Significant relationships were found in the ASD group between several GLU and GLN kinetic markers and AQ subscores (e.g., attention to detail, attention switching and/or communication) and word fluency (p < 0.05). Conclusions: Disturbances in GLN and GLU metabolism in ASD are associated with changes in ASD subscores but less with neurocognitive dysfunction or mood changes. Funding Sources: None.